The integration of artificial intelligence in social science - Selma, Nehari (The International tax journal, 2026)
Recent years have witnessed significant technological advancements, particularly in the field of artificial intelligence (AI), which has become increasingly influential across numerous aspects of life. This growing influence extends to a variety of academic disciplines, including sociology. The present study examines how AI is applied within the field of sociology, with a focus on understanding its broader social implications. Furthermore, the research investigates the evolving relationship between humans and AI, emphasizing the importance of aligning technological innovation with societal and ethical values. It also underscores the growing engagement of the social sciences with this subject, aiming to pave the way for a future in which sociology can both harness the opportunities presented by AI and confront the emerging challenges within.